Kontribusi Usahatani Kakao terhadap Pendapatan Petani (Studi Kasus Di Subak Abian Suci Desa Gadungan Kecamatan Selemadeg Timur Kabupaten Tabanan) - SUWINASIH, NI MADE; DEWI, NI LUH PRIMA KEMALA; DEWI, IDA AYU LISTIA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Contribution of Cocoa Farming to Farmers' Income (Case Study in Subak Abian Suci Gadungan Village East Selemadeg District Tabanan Regency). Cocoa is a superior commodity for plantations that has an important role for the national economy, namely as a source of income, as a provider of employment and foreign exchange in the country that occupies the third position. This study aims to calculate the amount of contribution of cocoa farming to farmers' incomes in Subak Abian Suci, and to find out the obstacles faced by farmers in cocoa farming in Subak Abian Suci. Sample determination techniques using saturated sampling or census techniques. The sample in this study was determined by selecting all cocoa farmers who received seed assistance in 2011 which amounted to 30 cocoa farmers. The data collection was carried out in December 2021 until January 2022 in Subak Abian Suci, Banjar Pangkung Langkuas, Gadungan Village, East Selemadeg District, Tabanan Regency. The analysis of data used to calculate farmers' sources of income is by analyzing agricultural income. The results showed that the highest source of income for farmers was cocoa farming income in 2021, which was an average income of Rp 15,411,838 /year with an average arable area of 0.39 Ha and a contribution of 42.57% of the total farmer's income of Rp 36. 199,745/year. The obstacles faced by farmers in cocoa farming in Subak Abian Suci consist of technical barriers, namely disease and climate pests and non-technical barriers, namely difficulty accessing information technology. Suggestions that need to be considered are that members in Subak Abian Suci maintain cocoa farming and develop cocoa farming by utilizing technological developments in cocoa farming to be able to compete with other products and improve cocoa quality. Should carry out more intensive cocoa plant care to deal with pests of diseases and erratic weather.